A multi centre randomized open label trial of chloroquine for the treatment of adults with SARS-CoV-2 infection in Vietnam - Kestelyn, E; Dung, NTP; Lam Minh, Y; Hung, LM; Quan, NM; Dung, NT; Minh, NNQ; Xuan, TC; Phong, NT; Ninh Thi Thanh, V; Donovan, J; Tu, TNH; et al. (F1000Research, 2020)
Background: COVID-19 is a respiratory disease caused by a novel coronavirus (SARS-CoV-2) and causes substantial morbidity and mortality. There is currently no vaccine to prevent COVID-19 or therapeutic agent to treat COVID-19. This clinical trial is designed to evaluate chloroquine as a potential therapeutic for the treatment of hospitalised people with COVID-19. We hypothesise that chloroquine slows viral replication in patients with COVID-19, attenuating the infection, and resulting in more rapid decline of viral load in throat/nose swabs. This viral attenuation should be associated with improved patient outcomes. Method: The study will start with a 10-patient prospective observational pilot study following the same entry and exclusion criteria as for the randomized trial and undergoing the same procedures. The main study is an open label, randomised, controlled trial with two parallel arms of standard of care (control arm) versus standard of care with 10 days of chloroquine (intervention arm) with a loading dose over the first 24 hours, followed by 300mg base orally once daily for nine days. The study will recruit patients in three sites in Ho Chi Minh City, Vietnam: the Hospital for Tropical Diseases, the Cu Chi Field Hospital, and the Can Gio COVID hospital. The primary endpoint is the time to viral clearance from throat/nose swab, defined as the time following randomization until the midpoint between the last positive and the first of the negative throat/nose swabs. Viral presence will be determined using RT-PCR to detect SARS-CoV-2 RNA. Discussion: The results of the study will add to the evidence-based guidelines for management of COVID-19. Given the enormous experience of its use in malaria chemoprophylaxis, excellent safety and tolerability profile, and its very low cost, if proved effective then chloroquine would be a readily deployable and affordable treatment for patients with COVID-19. Trial registration: Clinicaltrials.gov NCT04328493 31/03/2020